Internalization of Islamic Boarding School Values and Their Implications for the Formation of Student Discipline - Muhamad Muzaki; Mohammad Maulana Nur Kholis; Saiful Bahri; Nur Kabibuloh; Wahyu Dwi Wiyono (Journal of Educational Management Research, 2026)
Islamic boarding schools (pesantren) in Indonesia play a pivotal role in shaping students' character and moral values, especially in the face of globalization and societal shifts. This study explores the process of internalizing Islamic values at Al Ghozali Islamic Boarding School in Bogor, focusing on its systematic approach to character education. The research identifies three main stages of value internalization: value transformation, value transaction, and value transinternalization, which collectively contribute to the development of disciplined and responsible students. The study employs a qualitative research design, using participatory observation, in-depth interviews, and documentation to collect primary data. The findings indicate that the integration of formal and non-formal education, coupled with role modeling by caregivers, plays a crucial role in instilling values such as discipline, responsibility, and sincerity. This research contributes to the field of character education by demonstrating the practical implementation of value internalization in pesantren and provides insights for improving character education programs in other educational settings. The study also highlights the challenges of adapting traditional methods in the modern digital age.